STUDI TENTANG STRATEGI PENGGUNAAN MEDIA DIGITAL BERBASIS WEB DI KAK SETO SCHOOL PONDOK AREN TANGERANG SELATAN - Meydina Salsabila; Atin Fatimah; Siti Khosiah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The advancement of information and communication technology has encouraged the use of web-based digital media in early childhood learning to make it more interactive, flexible, and suited to students' needs. This study aims to describe the strategy for using web-based digital media at Kak Seto School Pondok Aren, South Tangerang, covering the purpose of use, teachers' steps in developing strategies, the types of media used, its advantages and disadvantages, and the challenges faced by teachers. The study used a descriptive qualitative method with a case study approach. The research subjects were first-grade students, teachers, and the school principal. Data were collected through observation, interviews, documentation, and field notes, then analyzed through data reduction, data display, and conclusion drawing, with validity tested through source and technique triangulation. The results show that web-based digital media is used to create interactive, enjoyable learning and to build digital literacy from an early age. Teachers' strategies are developed through planning, implementation, and evaluation stages, using media such as Baamboozle, Wordwall, Wayground, Zep, and Google Web. This media provides many advantages in increasing students' interest and engagement, but also presents challenges such as internet connection disruptions and screen time duration that must be managed wisely by teachers